Phytochemical Investigation for the Main Active Constituents in Arctium lappa L. Cultivated in Iraq - A.Al-Shammaa, Dhuha; Y. Saour, Kawkab; M. Abdul-Khalik, Zaid (Iraqi Journal of Pharmaceutical Sciences, 2017)
Burdock ( Arctium lappa), is among the most popular plants in traditional medicine and it is associated with several biological effects. Literature survey revealed the presence of phenylpropanoid compounds .The most widespread are hydroxycinnamic acids ( mainly caffeic acid and chlorogenic acid) and lignans (mainly arctiin and arctigenin). This work will confirm the presence of these compounds in Arctium lappa, cultivated in Iraq, in both root and leaf samples. The dried plant samples were extracted by soxhlet with 80% methanol then separated the main constituents by thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). Identification of the isolated compounds was carried out by UV, IR, and compared with reference standards using TLC, HPLC and HPTLC.Keywords: Actium lappa, hydroxycinnamic acid, Lignan, Phytochemical.